Desain Didaktis Perkalian Bilangan Cacah untuk Memfasilitasi Kemampuan Numerasi Peserta Didik Kelas III - Dita Mulyani Asih; Dindin Abdul Muiz Lidinillah; Ika Fitri Apriani (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study was motivated by the findings of learning obstacles experienced by students in the multiplication of count numbers. The findings were obtained through the learning obstacle test at the preliminary study stage and supported by data showing the low numeracy skills of students in Indonesia. The identified difficulties include: (1) understanding the meaning of story problems, (2) understanding the concept of multiplication as repeated addition, (3) performing mathematical calculation processes, and (4) applying the concept of multiplication in everyday life. To overcome these problems, a didactical design was developed as an effort to minimize learning obstacles while facilitating students' numeracy skills. This research uses the Didactical Design Research (DDR) method which includes three stages, namely prospective analysis, metapedidactic, and retrospective. Data were collected through observation interviews, tests, questionnaires, and documentation studies, then analyzed through data reduction, presentation and verification. The results showed that the application of didactical design had a positive impact on multiplication learning. This is evidenced by 89% of students who gave positive responses, as well as the reduction of learning barriers that had previously been identified, especially the reduction of difficulties in understanding the concept of multiplication. However, there are still some aspects that need to be improved to optimize learning and anticipate other potential obstacles.